PRODUCTION PROCESS OPTIMIZATION OF MASARO FERTILIZER - Fakhri Nabiel Aslam, Muhammad
Waste is an urgent environmental problems of Indonesia. BPS (2018) stated that Indonesia generated 65 million tonnes of waste in 2016. Additionally, Indonesia is also facing overdependence on synthetic fertilizers (nearly 8,5 million tonnes in 2019). Without reducing their usage, synthetic fertilizers will continue to burden the nation’s budget through subsidies and strip farmlands of their nutrients. One effort to solve both problems simultaneously is MASARO (Manajemen Sampah Zero), with its main product, MASARO fertilizer. MASARO fertilizer is made from the fermentation of organic waste, assisted by MASARO catalyst. Currently, the production process of MASARO’s fertilizer has not been well quantified: the process control still depends on human senses (visual, olfactory). The optimal operating conditions are yet to be known, conditions that result in higher reaction rates and better product quality. Lastly, there has not been an analysis of the main contents of MASARO fertilizer, which are amino acids and microbes. Thus, this research was conducted to quantify the production parameters and the contents of MASARO fertilizer. In the production experiments, waste was finely shredded, added to water, and then reacted in step I and step II. Each reaction was assisted by MASARO catalyst I and II. In step I, carbohydrate and protein are fermented into organic adic and amino acid, respectively. Then, in step I, amino acid decomposes into ammonia when the organic acid was spent by the bacteria. The optimal production process is with a dark bioreactor. Waste’s content is at 40% of the reactor’s volume, mixed once per day, and not aerated. Step I is stopped when the pH of the reaction mixture is stable within the range of 4,5 until 4,8. Then, step II was stopped when the fertilizer’s pH change by 0,3 from the previous step.